Use of text messages to communicate clinical recommendations to health workers in rural China: a cluster-randomized trial - Yaolong Chen; Kehu Yang; Tao Jing; Jinhui Tian; Xiping Shen; Changchun Xie; Bin Ma; Yali Liu; Liang Yao; Xiaoyuan Cao (The World Health Organization, 2014)
Objective To compare the effectiveness of mobile phone text messaging and that of traditional health worker training in communicating clinical recommendations to health workers in China. Methods A cluster-randomized controlled trial (Chinese Clinical Trial Register: ChiCTR-TRC-09000488) was conducted in 100 township health centres in north-western China between 17 October and 25 December 2011. Health workers were allocated either to receive 16 text messages with recommendations on the management of viral infections affecting the upper respiratory tract and otitis media (intervention group, n = 490) or to receive the same recommendations through the existing continuing medical education programme - a one-day training workshop (control group, n = 487). Health workers' knowledge of the recommendations was assessed before and after messaging and traditional training through a multiple choice questionnaire. The percentage change in score in the control group was compared with that in the intervention group. Changes in prescribing practices were also compared. Findings Health workers' knowledge of the recommendations increased significantly in the intervention group, both individually (0.17 points; 95% confidence interval, CI: 0.168-0.172) and at the cluster level (0.16 points; 95% CI: 0.157-0.163), but not in the control group. In the intervention group steroid prescriptions decreased by 5 percentage points but antibiotic prescriptions remained unchanged. In the control group, however, antibiotic and steroid prescriptions increased by 17 and 11 percentage points, respectively. Conclusion Text messages can be effective for transmitting medical information and changing health workers' behaviour, particularly in resource-limited settings.